2015
DOI: 10.1007/s11883-015-0509-6
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Signaling in the Vasculature

Abstract: Despite their discovery as angiogenic factors and mitogens for endothelial cells more than 30 years ago, much remains to be determined about the role of fibroblast growth factors (FGFs) and their receptors in vascular development, homeostasis, and disease. In vitro studies show that members of the FGF family stimulate growth, migration, and sprouting of endothelial cells, and growth, migration, and phenotypic plasticity of vascular smooth muscle cells. Recent studies have revealed important roles for FGFs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 103 publications
1
58
0
1
Order By: Relevance
“…Although these protein isoforms are identified in pathological conditions like cancer, Alzheimer's disease and atherosclerosis, the mechanisms and significance of ASE-mediated production of isoforms in the pregnant UA are yet to be investigated. It is important to note that the above-mentioned protein isoforms are known to interact with the phosphatidylinositol signaling system, which has a unique physiological role in vascular endothelial and smooth muscle contraction [78][79][80][81][82][83]. Besides, this study revealed that differential splicing occurred in a small subset of DEGs (40 upregulated and 61 downregulated genes), suggesting that splicing may contribute to the differential expression of these genes.…”
Section: Discussionmentioning
confidence: 65%
“…Although these protein isoforms are identified in pathological conditions like cancer, Alzheimer's disease and atherosclerosis, the mechanisms and significance of ASE-mediated production of isoforms in the pregnant UA are yet to be investigated. It is important to note that the above-mentioned protein isoforms are known to interact with the phosphatidylinositol signaling system, which has a unique physiological role in vascular endothelial and smooth muscle contraction [78][79][80][81][82][83]. Besides, this study revealed that differential splicing occurred in a small subset of DEGs (40 upregulated and 61 downregulated genes), suggesting that splicing may contribute to the differential expression of these genes.…”
Section: Discussionmentioning
confidence: 65%
“…This may be due to the timeframe in which this kinase activity was measured or the single‐cell type evaluated. The importance of FGF2 in angiogenesis has been well established . In one study of FGF‐2 deficient mouse endothelial cells, FGF‐2 activation of ERK signaling was required for cell migration .…”
Section: Discussionmentioning
confidence: 99%
“…The importance of FGF2 in angiogenesis has been well established. 38 In one study of FGF-2 deficient mouse endothelial cells, FGF-2 activation of ERK signaling was required for cell migration. 39 Comparatively little work has been done on CH3L1 (also known as YKL-40, a heparin-binding glycoprotein), but due to its role in cancer, CH3L1 has been characterized in the context of tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts : Another supporting cell that plays a vital role in angiogenesis is the fibroblast, whose primary function is to synthesize and maintain the extracellular matrix, mostly by secreting collagen . In particular, they become activated and secrete various collagens in response to wounding . Fibroblast‐derived matrix proteins such as collagen 1 and procollagen C‐endopeptidase enhancer 1 are critical for the increased stiffness of the extracellular matrix which further induces the vasculature lumen formation .…”
Section: Design Consideration: How Simple Is Complex Enough?mentioning
confidence: 99%